PEMANTAPAN PSYCHOLOGICAL SELF CONCEPT PESERTA DIDIK MINORITAS MELALUI KONSELING LINTAS BUDAYA DAN AGAMA - Fatrida Anugrah Syafri; Muhammad Rifa'i Subhi (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2017)
This study aimed to describe the efforts of school counselor in establishing the Psychological Self Concept learners from minority cultural backgrounds in schools through counseling across cultures and religions. The subjects were students of class VII MTsN II Yogyakarta. At this time, students still bring cultural and religious upbringing of his childhood. Results showed that the influence of childhood subject in the establishment of Psychological Self Concept and the role of the school counselor effect, by providing guidance and counseling services which is based on social, cultural and religious and result conceptual steady against self-concept and improve aspects of the diversity of learners.